2020
DOI: 10.1111/ocr.12376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ovariectomy on maxilla and mandible dimensions of female rats

Abstract: Objective: The role of oestrogen in craniofacial growth still remains unclear. Therefore, the present study aimed to assess the effect of oestrogen deficiency on maxilla and mandible dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The success of the surgical procedure was confirmed by the animals' survival, gradual increase in body weight during the experimentation period and by the uterine atrophy after euthanasia in the experimental group (Omori et al, 2020). The decrease in endogenous estrogen release, caused by ovariectomy, provides significant differences in the body weight and uterine weight (Chen et al, 2014).…”
Section: Hypoestrogenism -Estrogen Deficiency Modelmentioning
confidence: 90%
See 2 more Smart Citations
“…The success of the surgical procedure was confirmed by the animals' survival, gradual increase in body weight during the experimentation period and by the uterine atrophy after euthanasia in the experimental group (Omori et al, 2020). The decrease in endogenous estrogen release, caused by ovariectomy, provides significant differences in the body weight and uterine weight (Chen et al, 2014).…”
Section: Hypoestrogenism -Estrogen Deficiency Modelmentioning
confidence: 90%
“…To create estrogen deficiency (decrease the endogenous production of estrogen), a bilateral surgical excision of the ovaries (ovariectomy) was performed in the hypoestrogenism group. While the control group was submitted to fictitious surgery, in which the ovaries were moved and returned to their initial position, as previously described in Omori et al (2020).…”
Section: Hypoestrogenism -Estrogen Deficiency Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a reported study on Japanese quails, E2-induced osteoclastogenesis can be regulated in the bone marrow cells via the RANK/RANKL/OPG (RANK/RANK Ligand/Osteoprotegerin) system during medullary bone formation ( Hiyama et al, 2019 ). Moreover, in prepubertal ovariectomy mice, E2 deficiency can promote both maxilla and mandible growth, accompanied by an increase in RANKL/OPG ratio ( Omori et al, 2020 ; Küchler et al, 2021 ). A low bone turnover in 20-day-old rats treated with E2 for 14 d was due to decreased bone remodeling ( Zhang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, previous studies reported the impact of estrogen on oral and dental tissues. It was reported that estrogen deficiency altered the gene expression involved in craniofacial growth sites and odontogenic area leading to alterations in the jaws bone length, condylar growth and morphological deterioration of tooth structure, respectively [9][10][11]. These effects are mediated by estrogen receptors (ERs) that are one of the ligand-activated transcription factors which control the cellular differentiation and growth.…”
Section: Introductionmentioning
confidence: 99%